Measuring patients' health and suffering – the first stages of instrument development. Issue 4 (31st May 2018) - Andermo, Susanne; Sundberg, Tobias; Falkenberg, Torkel; Nordberg, Johanna Hök; Arman, Maria
Abstract : Background: Patients have reported unanticipated and transformative health changes in existential character after integrative healthcare rehabilitation. Although there are several instruments measuring patients' experiences of health, identified instruments do not sufficiently capture patients' experiences of health and suffering after integrative health care. From a caring science perspective, health and suffering are understood as an integral part of human life. The objective of this study was to develop a first version of an instrument to measure patients' experiences of health and suffering, focusing on existential signs. Methods: This Swedish study used a methodological design with three iterative phases for instrument development. Firstly, an item pool was developed based on qualitative patient interviews (n = 64). Subsequently, the relevance of the items was explored in two rounds of cognitive patient interviews (n = 5 and n = 3). Finally, expert consultations (n = 5) were used to further refine the instrument. The construct of the instrument, its dimensions and domains emerged through the iterative development process. Results: The first phase development of the instrument resulted in two inter‐related overarching dimensions: existential signs of 'Health' and 'Suffering', characterised by five domains: 'Life passion and energy', 'Personal freedom', 'Relationships', 'Presence in life' and 'Meaning'. Instrument items were formulated using contemporary language and word pairs to reflect a movement and relation between health and suffering. The cognitive interviews and expert opinions helped refine items and domains. Conclusions: The dimensions, domains and items of the instrument 'Existential signs of health and suffering' are well represented in caring science theories. Further clinical implementation and evaluation of the instrument, including psychometric properties, will allow for greater diversity in terms of context generalisability and patient characteristics. The instrument is anticipated to be of value for evaluations in research, development of healthcare practice and theory development in caring science.